A new phytophagous species of Eurytoma (Hymenoptera: Eurytomidae) attacking Werauhia gladioliflora (Bromeliales: Bromeliaceae) - Gates, Michael W.; Cascante-Marin, Alfredo (Zootaxa, 2004)
Eurytoma werauhia Gates, new species, is described and illustrated. This species was reared from the floral buds of Werauhia gladioliflora (Wendl.) (Bromeliales: Bromeliaceae), in Costa Rica. This plant represents a new host record for the genus. Eurytoma werauhia is compared with other known species of Eurytoma, primarily due to its host and metasomal coloration.